Analisis Yuridis SEMA No. 3 Tahun 2023 Terhadap Kasus Perceraian di Pengadilan Agama Stabat - Ramadani; Syahrul Affan (Peduli Riset dan Pengabdian Masyarakat, 2024)
The increase in the number of divorce cases always increases significantly every year, even though divorce is a right for everyone who is married, of course it is something that should be avoided. In order to make divorce more difficult, the Religious Chamber of the Supreme Court then set benchmarks for granting divorce claims in the religious court environment by issuing Supreme Court Circular Letter No. 3 in 2023, in order to be able to reduce the divorce rate, which always increases every year. Then of course to find out the impact of implementing SEMA No. 3 of 2023 regarding the handling of divorce cases in the Stabat Religious Court requires in-depth research with the aim of providing concrete data about the effectiveness of the latest regulations on divorce cases that occur in Langkat district. By using a qualitative research approach, in order to gain understanding and describe conditions in a complex manner, the collection of data sources and data analysis were taken from the results of observations, documentation and interviews, resulting in several research results, namely that there is a significant difference in the number of divorces before 2023 with the number divorce after 2023 and there are clear juridical reasons for refusing to handle cases in order to implement the principle of making divorce difficult from judges and legal practitioners.